Iatrogenic parasitic myoma with two recurrence times after subsequent myomectomy: A rare and complicated case report - Pei- Chen Li; Ming- Hsing Lee; Yu- Chi Wei; Yung- Hsiang Hsu; Mun- Kun Hong (Gynecology and Minimally Invasive Therapy, 2020)
Increasing number of parasitic myoma (PM) cases due to specimen morcellation during minimally invasive surgery have been reported. The patient was a 46-year-old woman receiving laparoscopic subtotal hysterectomy due to fibroids. She was diagnosed as having PM and had two recurrences after subsequent myomectomies. To prevent recurrence, specimen-contained morcellation was performed during the myomectomies and postoperative ulipristal acetate was given, but with no effects. The interval between each recurrence decreased. Progressive lower abdominal pain and prominent vessels on the myoma were the two distinct clinical characteristics that differentiated PM from general myoma. This case study highlights the importance of specimen containment before morcellation in minimally invasive surgery and implies that the pathogenesis of PM recurrence is unknown.